Integration of transcriptome and metabolome analyses reveals key lodging-resistance-related genes and metabolic pathways in maize - Liu, Lei; Liu, Songtao; Lu, Haibo; Tian, Zaimin; Zhao, Haichao; Wei, Dong; Wang, Shuo; Huang, Zhihong (Frontiers in Genetics, 2022)
Stalk lodging, or breakage of the stalk at or below the ear, is one of the vital factors causing substantial yield losses in maize (Zea mays. L). Lodging affects maize plants’ physiological and molecular processes, eventually impacting plant growth and productivity. Despite this known fact, few researchers have investigated the genetic architecture underlying lodging in maize. Herein, through integrated transcriptome, metabolome, and phenotypic analyses of stalks of three diverse hybrid cultivars (highly resistant JNK738, mildly resistant JNK728, and lowly resistant XY335) at the tasseling (10 days to silking, 10 DTS) stage, we identified key genes and metabolic pathways modulating lodging resistance in maize. Based on the RNA-Seq analysis, a total of 10093 differentially expressed genes (DEGs) were identified from the comparison of the three varieties in pairs. Additionally, key lodging resistance–related metabolic pathways were obtained by KEGG enrichment analysis, and the DEGs were found predominantly enriched in phenylpropanoid and secondary metabolites biosynthesis pathways in the L_vs._H and M_vs._H comparison groups. Moreover, K-means analysis clustered the DEGs into clear and distinct expression profiles for each cultivar, with several functional and regulatory genes involved in the cell wall assembly, lignin biosynthetic process and hormone metabolic process being identified in the special clusters related to lodging resistance. Subsequently, integrating metabolome and transcriptome analyses revealed nine key lignin-associated metabolites that showed different expression trends in the three hybrid cultivars, among which L-phenylalanine and p-coumaric acid were regarded as differentially changed metabolites (DCMs). These two DCMs belonged to phenylalanine metabolism and biosynthesis pathways and were also supported by the RNA-Seq data. Furthermore, plant hormone signal transduction pathway–related genes encoding auxin, abscisic acid, jasmonates, and salicylic acid were differentially expressed in the three comparisons of lodging resistance, indicating these DEGs were valuable potential targets for improving maize lodging resistance. Finally, comparative physiological and qRT-PCR analyses results supported our transcriptome-based findings. Our research not only provides a preliminary theoretical basis and experimental ideas for an in-depth study of the regulatory networks involved in maize lodging resistance regulation but also opens up new avenues for molecular maize stalk lodging resistance breeding.